2021
DOI: 10.1371/journal.pbio.3001480
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in LRRK2 linked to Parkinson disease sequester Rab8a to damaged lysosomes and regulate transferrin-mediated iron uptake in microglia

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) cause autosomal dominant Parkinson disease (PD), while polymorphic LRRK2 variants are associated with sporadic PD. PD-linked mutations increase LRRK2 kinase activity and induce neurotoxicity in vitro and in vivo. The small GTPase Rab8a is a LRRK2 kinase substrate and is involved in receptor-mediated recycling and endocytic trafficking of transferrin, but the effect of PD-linked LRRK2 mutations on the function of Rab8a is poorly understood. Here, we show that ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 75 publications
2
52
0
Order By: Relevance
“…With regard to microglia, both in vitro and in vivo studies show that LRRK2 modulate microglia inflammatory responses. 53,55,56,[151][152][153] Recent studies suggest that LRRK2 levels in microglia may not have a direct effect on neuroinflammation in PD, as in vivo injection of a high acute dose of LPS failed to increase microglia LRRK2 protein levels in R1441C and G2019S young adult mice 70 . Similar results have been observed ex vivo, with neither LPS 154 or priming with a-syn pre-formed fibrils 155 increasing LRRK2 protein expression in cultured murine microglia.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to microglia, both in vitro and in vivo studies show that LRRK2 modulate microglia inflammatory responses. 53,55,56,[151][152][153] Recent studies suggest that LRRK2 levels in microglia may not have a direct effect on neuroinflammation in PD, as in vivo injection of a high acute dose of LPS failed to increase microglia LRRK2 protein levels in R1441C and G2019S young adult mice 70 . Similar results have been observed ex vivo, with neither LPS 154 or priming with a-syn pre-formed fibrils 155 increasing LRRK2 protein expression in cultured murine microglia.…”
Section: Discussionmentioning
confidence: 99%
“…150 With regard to microglia, both in vitro and in vivo studies show that LRRK2 modulate microglia inflammatory responses. 53,55,56,[151][152][153] Recent studies suggest that LRRK2 levels in microglia may not have a direct effect on neuroinflammation in PD, as in vivo injection of a high acute dose of LPS failed to increase microglia LRRK2 protein levels in R1441C and G2019S young adult mice 70 . Similar results have been observed ex vivo, with neither LPS 154 or priming with a-syn pre-formed fibrils 155 increasing LRRK2 protein expression in cultured murine microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Lin and their colleagues found that DJ-1 regulated microglial activation in response to lipopolysaccharide (LPS) treatment. DJ-1 deficiency in microglia increases the neurotoxicity induced by LPS (Mamais et al, 2021).…”
Section: Microglia and Pdmentioning
confidence: 99%